Pengaruh Perceived Overqualification dan Work Stress Dengan Moderasi Transformational Leadership Terhadap Innovative Work Behavior dan Turnover Intention - Rahmadhini Dwi Hadiyanti; Abdul Haeba Ramli (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze and explore the influence of two key factors, namely Perceived Overqualification and Work Stress, on employee Innovative Work Behavior and Turnover Intention in the context of logistics companies. In addition, this research considers the moderating role of Transformational Leadership in the relationship between Perceived Overqualification and Work Stress with Innovative Work Behavior and Turnover Intention. This research involved a survey of employees at a logistics company using a questionnaire, then the data collected was analyzed using quantitative methods with the population in this study involving 180 employees at a multinational logistics company that provides warehousing and distribution services in the Bekasi Regency area. The research results show that Perceived Overqualification and Work Stress have an influence on Turnover Intention. Apart from that, Transformational Leadership has been proven to moderate the relationship between Perceived Overqualification and Innovative Work Behavior. These results indicate that human resource management in logistics companies must consider Perceived Overqualification and Work Stress as important factors in promoting innovative work behavior that can reduce employee turnover intentions. This research has practical implications for logistics companies in developing more effective and efficient human resource management policies. Apart from that, this research also provides theoretical contributions in understanding the relationship between Perceived Overqualification, Work Stress, Transformational Leadership, Innovative Work Behavior and Turnover Intention in the context of logistics companies.